Performance analysis of the community meeting hall at Mountain Village: A case at Garawastu - Agustian, Renaldi; Hartati, Noviar Dwi; Sugih, Ageng; Rifai, Andri Irfan (Indonesian Journal of Multidisciplinary Science, 2024)
The meeting hall is used for community deliberation, security, and a gathering place for other activities. One of them is the meeting hall in Cipari Hamlet, Garawastu Village, but the condition of the meeting hall is not suitable for use. So that community services hamper the performance of the meeting hall. This study aims to analyze the performance of the Hamlet meeting hall for community services and determine the level of importance and community satisfaction with the performance of the meeting hall. The research methods used in this research are qualitative methods and quantitative methods. The data needed in this research include questionnaires and visual surveys. Thus, the output expected in this study is in the form of priority levels and data on proposed improvements to the Hamlet hall, which is the result of this IPA method). The average importance value is 5.31, while the average satisfaction value is 5.34, and the average gap value is -0.0388. Quadrant IV is a quadrant with high satisfaction and top priority importance. So, it is necessary to improve the suitability of the meeting hall for community services, and the village government also needs to increase responsiveness to community complaints.